An artificial lens material and its preparation method and application

Drug therapy in the prior art is solved by coating photoresponsive mesoporous silica-encapsulated MXene loaded with cell proliferation inhibitors, cadmium or nickel-doped MXene on the intraocular lens, combined with photothermal therapy and drug sustained release The problem of poor photothermal therapy has achieved efficient PCO prevention and treatment and reduced toxic side effects.

CN115708895BActive Publication Date: 2025-01-14SUZHOU BEIKE NANO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211551843.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-01-14
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

The existing drug treatment and photothermal therapy are not effective in preventing and treating post-onset cataracts (PCO). The drug is unstable, has a strong toxic effect, insufficient temperature of photothermal therapy, and triggers an inflammatory response, resulting in low prevention and treatment efficiency of PCO.

Method used

The surface coated with photoresponsive mesoporous silica-encapsulated MXene loaded with cell proliferation inhibitors, cadmium or nickel-doped MXene combined with photothermal therapy and drug sustained release to alleviate inflammatory response and improve inflammatory response Prevention and treatment efficiency.

Benefits of technology

It achieves efficient cell killing and drug sustained release, reduces toxic side effects, significantly improves the prevention and treatment efficiency of PCO, and does not affect the light transmittance and refractive index of the intraocular lens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115708895B_ABST
    Figure CN115708895B_ABST
Patent Text Reader

Abstract

The present application relates to the fields of nanomaterial technology and biomedicine, and specifically to an artificial lens material, a preparation method and an application thereof. An artificial lens material, wherein the posterior surface of the optical zone of the artificial lens is coated with a photoresponsive mesoporous silica-encapsulated MXene doped with a cell proliferation inhibitor, cadmium or nickel. The application of the artificial lens material prepared by the preparation method in the preparation of materials for the treatment or prevention of secondary cataracts. The present application achieves a combined therapy of photothermal therapy and sustained drug release to prevent and treat secondary cataracts by coating the posterior surface of the optical zone of the artificial lens with a photoresponsive mesoporous silica-encapsulated MXene doped with a cell proliferation inhibitor, cadmium or nickel, and has high biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the fields of nanomaterial technology and biomedicine, and specifically to an artificial lens material and a preparation method and application thereof. Background Art

[0002] Posterior capsular opacification (PCO) is the most common complication affecting vision after cataract extraction combined with intraocular lens implantation. Its incidence in adults is 30%-50% (within 5 years), of which about 20%-30% of patients become blind again due to PCO, and 43% of patients need another surgery due to PCO. The incidence of PCO in children is as high as 100%.

[0003] After cataract removal, an artificial lens is implanted in the retained lens bag to restore the patient's postoperative visual function. However, part of the artificial lens remaining in the anterior capsule will proliferate under the stimulation of the postoperative inflammatory response, and crawl between the posterior lens capsule and the posterior surface of the artificial lens through epithelial-mesenchymal transformation, causing opacity of the refractive medium and shrinkage of the posterior capsule. The occurrence of PCO can cause secondary loss of visual function and requires further treatment, such as laser posterior capsulotomy. Laser treatment is expensive and there are risks after surgery.

[0004] The methods for preventing and treating PCO generally include: artificial lens design, improved surgical techniques, laser posterior capsulotomy, physical and chemical methods. Currently, physical and chemical methods are the hot spots in the research of PCO prevention and treatment.

[0005] Physical methods include removing residual lens epithelial cells on the capsule as much as possible during or after surgery, hyperosmotic pressure therapy, and photothermal therapy. Chemical methods include various cell proliferation inhibitors during and after surgery. Despite this, the effectiveness of PCO prevention and treatment is still not ideal, and there is currently no clinical method that can effectively prevent and treat PCO.

[0006] Chemical drugs are another common way to prevent and treat PCO. Chemical drugs, such as nonsteroidal anti-inflammatory drugs (NSAIDs), such as COX-1 or COX-2 inhibitors, 5-fluorouracil (5-FU), methotrexate (MTX), epidermal growth factor inhibitors, such as gefitinib, erlotinib, cyclosporine A (CsA), tacrolimus, rapamycin, paclitaxel, ROCK signaling pathway inhibitors, transforming growth factor β (TGF-β) inhibitors, and / or siRNA and miRNA of the above signaling molecules, can be used to prevent and treat PCO through a variety of administration methods, such as topical eye drops, intraoperative intracameral injection, perfusion, and intraocular sustained release using artificial lenses as carriers. Some drugs can achieve the effect of delaying the course of PCO.

[0007] Among the existing technologies, photothermal therapy is another promising method for the prevention and treatment of PCO. Photothermal therapy is based on photoconverters. Under the irradiation of lasers of a specific wavelength, photothermal agents can efficiently convert light energy into heat energy, killing tissue cells with high temperatures. However, according to literature reports, the current effectiveness of photothermal therapy in the prevention and treatment of PCO is only about 60%. In summary, neither drug therapy nor photothermal therapy can effectively prevent the occurrence of PCO.

[0008] The reasons why drug therapy and photothermal therapy cannot effectively prevent and treat PCO are summarized as follows: (1) Cell proliferation inhibitors applied to the surface of IOL in various ways cannot maintain drug sustained release for a long time. After a period of time, the anti-proliferation effect of lens epithelial cells disappears; (2) It is difficult to achieve a balance between the cell killing effect of the drug and the toxic effect of the drug on intraocular tissues, which can easily lead to intraocular side effects; (3) The photosensitizer is applied to the lateral annular outer edge of the intraocular lens, resulting in a gradual decrease in temperature from the outer edge to the center of the intraocular lens after irradiation with 808nm infrared light, resulting in a central temperature of less than 42℃-45℃, which cannot play an effective killing role and leads to turbidity in the visual axis area; (4) When photothermal killing cells, it can cause local inflammatory reactions. Inflammatory mediators will further stimulate the proliferation and migration of lens epithelial cells and promote the formation of PCO.

[0009] The applicant submitted an invention patent application in 2020, with the publication number CN114618019A, which records that a silver-doped MXene drug-carrying material is dip-coated onto the rear surface of an intraocular lens to obtain a self-sterilizing intraocular lens. However, the drug loading and drug loading stability of this method are not satisfactory to the inventor. Summary of the invention

[0010] The present invention provides an artificial lens material. The rear surface of the optical zone of the artificial lens is coated with MXene doped with a cell proliferation inhibitor, cadmium or nickel and wrapped with light-responsive mesoporous silica.

[0011] The photosensitizer photoresponsive mesoporous silica with high light transmittance and high photothermal conversion efficiency is loaded on the back surface of the artificial lens, and the cell proliferation inhibitor is also encapsulated to further reduce the inflammatory response caused by photothermal effect, improve the prevention and treatment efficacy of PCO, and realize photothermal therapy and drug sustained release to prevent and treat PCO.

[0012] In the artificial lens material, the cell proliferation inhibitor is preferably a non-steroidal anti-inflammatory drug. The non-steroidal anti-inflammatory drug may be, for example, a COX-1 inhibitor, a COX-2 inhibitor, 5-fluorouracil, methotrexate, an epidermal growth factor inhibitor gefitinib or erlotinib, cyclosporine A, tacrolimus, rapamycin, paclitaxel, a ROCK signaling pathway inhibitor, a transforming growth factor β inhibitor and / or siRNA or miRNA thereof.

[0013] The artificial lens material preferably has a mass ratio of 0.5:1 between the photoresponsive mesoporous silica and the MXene doped with a cell proliferation inhibitor, cadmium or nickel.

[0014] The artificial lens material preferably has a mass ratio of the cell proliferation inhibitor to the MXene doped with cadmium or nickel at 0.84:1.

[0015] In the artificial lens material, the molar ratio of the doped cadmium or nickel element to MXene is 0.005-0.05:1, preferably 0.01-0.02:1, and the most preferred ratio is 0.01:1.

[0016] The method for preparing the artificial lens material comprises the following steps:

[0017] (1) MXene doped with cadmium or nickel is surface-modified with polyethylene glycol, then covalently bound with RGD peptide, and loaded with cell proliferation inhibitors to obtain MXene loaded with cell proliferation inhibitors; (2) MXene loaded with cell proliferation inhibitors is mixed with photoresponsive mesoporous silica, added with deionized water, and stirred to obtain MXene loaded with cell proliferation inhibitors wrapped with photoresponsive mesoporous silica;

[0018] (3) MXene loaded with cell proliferation inhibitors and encapsulated by photoresponsive mesoporous silica is coated on the posterior surface of the intraocular lens optical zone.

[0019] The MXene doped with cadmium or nickel is obtained by the following steps:

[0020] (1) Preparation of MAX phase precursor: metal powder represented by M in the MAX phase, aluminum powder represented by A, and carbide or nitride powder corresponding to M are added to a ball mill according to proportion and ground, wherein an excess amount of aluminum powder is added, and after sufficient grinding, the mixture is transferred to an alumina crucible, covered with graphite foil, and placed in a tube furnace for heating and reaction under an inert atmosphere to obtain Al-M n+1 AX n Sintered blocks;

[0021] (2) Al-M n+1 AX nThe sintered block was fully ground to obtain the precursor phase powder, which was then soaked in hydrochloric acid and washed with deionized water to remove excess metal elements. After the washing was completed, the precipitate was taken out and dried in a vacuum drying oven to obtain Al-M n+ 1AX n Phase powder;

[0022] (3) Molten salt etching of Al-M n+1 AX n Phase powder to obtain MXene doped with cadmium or nickel: Take out the dried Al-MAX, put it into a ball mill with cadmium chloride or nickel chloride, sodium chloride and potassium chloride and grind it thoroughly. Put the ground mixed powder into an alumina crucible and place it in a tube furnace to react at high temperature under an inert atmosphere. After the reaction is completed, wash the reaction product with hydrochloric acid, filter out the solvent, take the precipitate and add deionized water for ultrasonic vibration. Then, repeatedly centrifuge and wash with deionized water to obtain MXene material doped with cadmium or nickel.

[0023] The molar ratio of MAX, cadmium chloride or nickel chloride, NaCl and KCl is 1:1-6:3:3; the temperature of the tube furnace is 550-850° C., and the reaction time is 4-10 hours.

[0024] Preferably, the photoresponsive mesoporous silica is obtained by the following steps:

[0025] Mix dodecanol, sodium hydroxide, hexadecyltrimethylammonium bromide and deionized water, heat and stir to obtain a mixed solution, add ethyl orthosilicate dropwise into the mixed solution, heat to react, collect the reaction product by centrifugation, wash, centrifuge again, and vacuum dry the precipitate to obtain the product.

[0026] The application of the artificial lens material in preparing materials for treating or preventing after-cataract.

[0027] The present application achieves a combined therapy of photothermal therapy and sustained drug release to prevent and treat post-cataracts by coating the posterior surface of the optical zone of an artificial lens with a photoresponsive mesoporous silica-encapsulated MXene loaded with a cell proliferation inhibitor, cadmium or nickel doped, and has high biocompatibility.

[0028] Photodynamic therapy using photoresponsive mesoporous silica-wrapped MXene doped with cell proliferation inhibitors, cadmium or nickel elements, uses infrared light irradiation to effectively kill cells while accurately controlling drug release to maintain effective drug concentrations for a longer period of time, thereby improving efficacy and reducing toxic side effects.

[0029] The photoresponsive mesoporous silica-wrapped MXene doped with cell proliferation inhibitors, cadmium or nickel elements provided in the present application will not affect the light transmittance and refractive index of the artificial lens, and has more practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The appearance of intraocular lenses loaded with different Ti3C2 concentrations (0μg / ml-500μg / ml) in response to light rapamycin;

[0031] Figure 2 is the light-controlled cumulative release curve of rapamycin;

[0032] Figure 3 The PCO situation is shown in the figure one month after the intraocular lenses coated with different treatments were implanted in rabbit eyes. DETAILED DESCRIPTION

[0033] This embodiment provides an artificial lens material, wherein the rear surface of the optical zone of the artificial lens is coated with a photoresponsive mesoporous silica-encapsulated MXene doped with a cell proliferation inhibitor, cadmium or nickel.

[0034] MXene is a graphene-like structure obtained by processing the MAX phase. The specific molecular formula of the MAX phase is M n+1 AX n (n=1,2or3), where M refers to transition metals from the first few groups, such as Sc, Ti, Zr, V, Nb, Cr or Mo; A refers to Al, and X refers to C and / or N. Since MX has a strong bond energy and A has a more active chemical activity, A can be removed from the MAX phase by etching to obtain a graphene-like 2D structure - MXene. When etching MAX using the molten salt method, cadmium salt or nickel salt is added to obtain MXene doped with cadmium or nickel.

[0035] Cd or Ni doped MXene can be obtained by the following steps:

[0036] (1) Preparation of MAX phase precursor: metal powder represented by M in the MAX phase, aluminum powder represented by A, and carbide or nitride powder corresponding to M are added to a ball mill according to proportion and ground, wherein an excess amount of aluminum powder is added, and after sufficient grinding, the mixture is transferred to an alumina crucible, covered with graphite foil, and placed in a tube furnace for heating and reaction under an inert atmosphere to obtain Al-M n+1 AX n ;

[0037] The specific operation can be: use a ball mill to grind the metal powder represented by M, the carbide or nitride powder corresponding to M, and the aluminum powder at a ratio of 1:2:1 (mass ratio) at 70 rpm for 18 hours, wherein the aluminum powder is excessive. Then, the ball-milled precursor powder is loaded into an alumina crucible, covered with graphite foil, and then placed in a tube furnace. The furnace is purged with argon for 30 minutes at room temperature, and the powder is heated to 1380°C and maintained at an argon flow rate of about 100 sccm for 2 hours;

[0038] Transition metals include but are not limited to Sc, Ti, V, Cr, Zr, Nb, Hf, and Ta. The corresponding mass ratio is 1:2:1, and one of the reactant powders is a combination of Ti, TiC, and Al powders in a mass ratio of 1:2:1. The prepared MAX phase ceramics include but are not limited to any one of Ti2AlC, Ti2AlN, V2AlC, V2AlN, Nb2AlC, Nb2AlN, Ta2AlC, Ti3AlC2, Ti3AlN2, V3AlC2, Ta3AlC2, Ta3AlN2, Ti4AlC3, Ti4AlN3, Ta4AlC3, Ta4NAl3, and Nb4AlC3, or a combination of two or more MAX phase ceramics;

[0039] (2) Al-M n+1 AX n The sintered block is fully ground to obtain MAX phase powder, which is then washed and filtered with hydrochloric acid and deionized water in a vacuum filtration device to remove excess metal elements. After washing, the precipitate is taken out and placed in a vacuum drying oven for drying;

[0040] Hydrochloric acid can be 9M HCl. Use hydrochloric acid to wash until no bubbles are generated. Generally, 500ml 9M HCl is enough to wash 50-60g Al-M n+1 AX n; The vacuum drying temperature can be 80°C;

[0041] (3) Molten salt method to etch MAX to obtain MXene doped with cadmium or nickel: Take out the dried MAX, put it into a ball mill with cadmium chloride or nickel chloride, sodium chloride and potassium chloride, and grind it thoroughly. Put the ground mixed powder into an alumina crucible, place it in a tube furnace, and react at high temperature under an inert atmosphere. After the reaction is completed, wash the reaction product with hydrochloric acid, filter out the solvent, take the precipitate and add deionized water for ultrasonic vibration. Then, repeatedly centrifuge and wash with deionized water to obtain MXene material doped with cadmium or nickel.

[0042] The molar ratio of the doped cadmium or nickel element to MXene is 0.005-0.05:1, preferably 0.01-0.02:1, and the most preferred ratio is 0.01:1.

[0043] The molar ratio of MAX, cadmium chloride or nickel chloride, NaCl and KCl is 1:1-6:3:3; the temperature of the tube furnace is 550-850° C., and the reaction time is 4-10 hours.

[0044] The cell proliferation inhibitor selected is a non-steroidal anti-inflammatory drug, such as a COX-1 or COX-2 inhibitor, 5-fluorouracil (5-FU), methotrexate (MTX), an epidermal growth factor inhibitor, such as gefitinib, erlotinib, cyclosporine A (CSA), tacrolimus, rapamycin, paclitaxel, a ROCK signaling pathway inhibitor, a transforming growth factor β (TGF-β) inhibitor, and / or siRNA and miRNA of the above signaling molecules. There is no special requirement for this in this embodiment, as long as the non-steroidal anti-inflammatory drug that can be used clinically can be used in this application. Preferably, rapamycin is used.

[0045] The artificial lens used can be hydrophobic acrylate, acrylate hydrogel, silicone, silicone hydrogel, fluorosilicone acrylate, polystyrene and polymethyl methacrylate, polycarbonate, polysiloxane, and / or a mixture thereof. There is no special requirement for this in this embodiment. As long as the artificial lens can be used clinically, it can be used in this application.

[0046] The photoresponsive mesoporous silica used is wrapped with a MXene doped with a cell proliferation inhibitor, cadmium or nickel, wherein the mass ratio of the photoresponsive mesoporous silica to the MXene doped with a cell proliferation inhibitor, cadmium or nickel is in the range of 0.02-1:1, the preferred ratio range is 0.2-0.6:1, and the preferred ratio is 0.4:1. The different mass ratios of the photoresponsive mesoporous silica and the MXene doped with a cell proliferation inhibitor, cadmium or nickel will affect the efficiency of the drug-loaded intraocular lens in inhibiting the proliferation of residual lens epithelial cells in the capsule. When the mass ratio of the photoresponsive mesoporous silica to the MXene doped with a cell proliferation inhibitor, cadmium or nickel is less than 0.02:1, the concentration of the cell proliferation agent, rapamycin, in the aqueous humor after the drug-loaded intraocular lens is implanted is too high, which will have a significant toxic effect on the intraocular tissue, causing corneal edema, damage to the iris, ciliary body and retina. When the mass ratio of photoresponsive mesoporous silica to MXene doped with cell proliferation inhibitors, cadmium or nickel is greater than 1:1, the concentration of rapamycin, a cell proliferation agent, in the aqueous humor after implantation of the drug-loaded intraocular lens is too low to inhibit the proliferation of residual lens epithelial cells in the capsular bag. When the mass ratio of photoresponsive mesoporous silica to MXene doped with cell proliferation inhibitors, cadmium or nickel is within the range of 0.2-0.6:1, the drug-loaded intraocular lens has the best effect in inhibiting cell proliferation without obvious intraocular toxicity.

[0047] The used MXene is loaded with cell proliferation inhibitors, cadmium or nickel doped elements, and the mass ratio of cell proliferation inhibitors to MXene doped with cadmium or nickel is in the range of 0.1-1.5:1, the preferred ratio range is 0.4-1:1, and the preferred ratio is 0.84:1. Doping the corresponding metal elements cadmium or nickel into the MXene material can enhance the performance of MXene. The enhancement effect is mainly reflected in the photothermal properties and high sensitivity of the MXene material, which is more beneficial to realize various applications such as photothermal tumor therapy, photodynamic therapy, photothermal drug release, etc.

[0048] The method for preparing the artificial lens material in this embodiment comprises the following steps:

[0049] (1) MXene doped with cadmium or nickel is surface-modified with polyethylene glycol, then covalently bound with arginine-glycine-aspartic acid (Arg-Gly-Asp, RGD) peptide, and loaded with cell proliferation inhibitors to obtain MXene loaded with cell proliferation inhibitors;

[0050] (2) mixing the MXene loaded with the cell proliferation inhibitor and the photoresponsive mesoporous silica, adding deionized water and stirring to obtain the MXene loaded with the cell proliferation inhibitor wrapped by the photoresponsive mesoporous silica;

[0051] (3) Mixing the MXene loaded with the cell proliferation inhibitor and the photoresponsive mesoporous silica, adding the mixture into deionized water and stirring. Since the MXene material has an electrostatic adsorption property, the MXene material can be adsorbed with the photoresponsive mesoporous silica to form a photoresponsive mesoporous silica-encapsulated MXene loaded with the cell proliferation inhibitor;

[0052] (4) The stirring rate can be 2000-3000 rpm, and the stirring time can be 24h;

[0053] (5) coating the photoresponsive mesoporous silica-encapsulated MXene loaded with a cell proliferation inhibitor onto the posterior surface of the intraocular lens optical zone;

[0054] (6) The anterior surface, side surface and lens loop of the intraocular lens optical zone were sealed with tape, leaving only the posterior surface of the lens optical zone exposed to the air, the intraocular lens was treated with O2 plasma for 5 minutes, immersed in Gemini surfactant for full combination, and then mixed with MXene loaded with cell proliferation inhibitors wrapped in photoresponsive mesoporous silica, and the MXene loaded with cell proliferation inhibitors wrapped in photoresponsive mesoporous silica was fixed to the posterior surface of the intraocular lens optical zone.

[0055] Photoresponsive mesoporous silica is obtained by the following steps:

[0056] Mix dodecanol, sodium hydroxide, hexadecyltrimethylammonium bromide and deionized water, heat and stir to obtain a mixed solution, add ethyl orthosilicate dropwise into the mixed solution, heat to react, collect the reaction product by centrifugation, wash, centrifuge again, and vacuum dry the precipitate to obtain the product.

[0057] The specific operation can be as follows: add 20 mg dodecanol, 30 mg sodium hydroxide, 0.1 g CTAB (hexadecyltrimethylammonium bromide) and 50 mL deionized water to a round-bottom flask, heat to 60°C and stir for 0.5 h. Then use a constant pressure drop funnel to drop 0.75 mL TEOS (tetraethyl orthosilicate) into the above solution, stir at 60°C for 2 h to allow TEOS to react completely. Collect the reaction product by centrifugation, wash with ethanol, and centrifuge again. Repeat four times to remove CTAB and dodecanol, and finally vacuum dry the precipitate.

[0058] The artificial lens material prepared above can be used to prepare materials for treating or preventing after-cataracts.

[0059] Two specific operation examples are provided below according to the order of material preparation. These operation examples are only used to explain the present application scheme, and the present application scheme is not limited to the operation examples.

[0060] Operation example 1

[0061] First, Ti, TiC, and Al were added to a ball mill at a mass ratio of 1:2:1 and ground at 70 rpm for 18 hours. After sufficient grinding, they were transferred to an alumina crucible, covered with graphite foil, and placed in a tube furnace. The furnace was purged with argon for 30 minutes at room temperature, and then heated to 1380°C at a heating and cooling rate of 3°C / min; cooled to room temperature, soaked and washed with 9M hydrochloric acid until no bubbles were generated, filtered with a vacuum filtration device, and then washed and filtered with deionized water. The precipitate was placed in a vacuum drying oven and dried at 80°C for at least 6 hours to obtain Al-Ti3AlC2;

[0062] Al-Ti3AlC2, cadmium chloride, sodium chloride and potassium chloride are added to a ball mill at a molar ratio of 1:6:3:3 and mixed and ground. After sufficient grinding, they are placed in an alumina crucible, placed in a tube furnace, and argon is introduced to maintain the reaction at 700°C for 6 hours. The reaction product is taken out, soaked in 10% dilute hydrochloric acid for 1 hour, the solution is filtered out with a vacuum filtration device and washed with deionized water, and the precipitate is taken out and ultrasonically shaken with deionized water for 1 hour. Then it is repeatedly centrifuged and washed with deionized water until the pH of the supernatant is 6, and finally centrifuged once more to obtain the cadmium-doped Ti3C2 material.

[0063] The obtained Ti3C2 material is surface-modified with polyethylene glycol, then covalently bonded with RGD polypeptide, and loaded with cell proliferation inhibitor (rapamycin), thereby obtaining Ti3C2 nanomaterial loaded with cell proliferation inhibitor (rapamycin);

[0064] Add 20 mg of dodecanol, 30 mg of sodium hydroxide, 0.1 g of CTAB (hexadecyltrimethylammonium bromide) and 50 mL of deionized water to a round-bottom flask, mix, heat to 60 ° C and stir for 0.5 h. Then use a constant pressure drop funnel to add 0.75 mL of TEOS (tetraethyl orthosilicate) dropwise to the above solution, stir at 60 ° C for 2 h to allow TEOS to react completely. Collect the reaction product by centrifugation, wash with ethanol, and centrifuge again. Repeat four times to remove CTAB and dodecanol, and finally vacuum dry the precipitate to obtain light-responsive mesoporous silica;

[0065] The Ti3C2 nanomaterial loaded with a cell proliferation inhibitor (rapamycin) was mixed with photoresponsive mesoporous silica, added into deionized water and stirred at 2000 rpm for 24 h. Since the MXene material has electrostatic adsorption properties, it can be adsorbed with the photoresponsive mesoporous silica to form a Ti3C2 system wrapped with photoresponsive mesoporous silica.

[0066] Finally, the anterior surface, side surface and lens loop of the intraocular lens optical zone were sealed with tape, leaving only the posterior surface of the lens optical zone exposed to the air. The intraocular lens was treated with O2 plasma for 5 minutes, immersed in Gemini surfactant for full combination, and then the drug-loaded Ti3C2 composite material was coated on the posterior surface of the intraocular lens.

[0067] Operation example 2

[0068] First, V, Al, and C were added to a ball mill at an atomic ratio of 2:1.5:1 and ground at 400 rpm for 18 hours. After sufficient grinding, they were transferred to an alumina crucible, covered with graphite foil and placed in a tube furnace. The furnace was purged with argon for 30 minutes at room temperature, and then heated to 1500°C at a rate of 5°C / min; cooled to room temperature, soaked and washed with 9M hydrochloric acid until no bubbles were generated, filtered with a vacuum filtration device, and then washed and filtered with deionized water. The precipitate was placed in a vacuum drying oven and dried at 60°C for at least 6 hours to obtain V2AlC with excess Al;

[0069] Al-V2AlC, nickel chloride, sodium chloride and potassium chloride are added to a ball mill at a molar ratio of 1:3:2:2 and mixed and ground. After sufficient grinding, they are placed in an alumina crucible, placed in a tube furnace, and argon is introduced to maintain the reaction at 700°C for 6 hours. The reaction product is taken out, soaked in 10% dilute hydrochloric acid for 1 hour, the solution is filtered out with a vacuum filtration device and washed with deionized water, and the precipitate is taken out and ultrasonically shaken with deionized water for 1 hour. Then, it is repeatedly centrifuged and washed with deionized water until the pH of the supernatant is 6, and finally centrifuged once more to obtain the nickel-doped V2C material.

[0070] The obtained V2C material is surface-modified with polyethylene glycol, then covalently bound with RGD polypeptide, and loaded with cell proliferation inhibitor (rapamycin), thereby obtaining V2C nanomaterial loaded with cell proliferation inhibitor (rapamycin);

[0071] Add 20 mg of dodecanol, 30 mg of sodium hydroxide, 0.1 g of CTAB (hexadecyltrimethylammonium bromide) and 50 mL of deionized water to a round-bottom flask, mix, heat to 60 ° C and stir for 0.5 h. Then use a constant pressure drop funnel to add 0.75 mL of TEOS (tetraethyl orthosilicate) dropwise to the above solution, stir at 60 ° C for 2 h to allow TEOS to react completely. Collect the reaction product by centrifugation, wash with ethanol, and centrifuge again. Repeat four times to remove CTAB and dodecanol, and finally vacuum dry the precipitate to obtain light-responsive mesoporous silica;

[0072] The V2C nanomaterial loaded with a cell proliferation inhibitor (rapamycin) was mixed with photoresponsive mesoporous silica, added into deionized water and stirred at 2000 rpm for 24 hours. Since the MXene material has electrostatic adsorption properties, it can be adsorbed with the photoresponsive mesoporous silica to form a photoresponsive mesoporous silica-encapsulated V2C system.

[0073] Finally, the anterior surface, side surface and lens loop of the intraocular lens optical zone were sealed with tape, leaving only the posterior surface of the lens optical zone exposed to the air. The intraocular lens was treated with O2 plasma for 5 minutes, immersed in Gemini surfactant for full combination, and then the drug-loaded V2C composite material was coated on the posterior surface of the intraocular lens.

[0074] Operation example 3

[0075] Ti, TiC and Al were ground at 70 rpm for 18 h in a mass ratio of 1:2:1, heated to 1380 °C, cooled to room temperature, soaked and washed with 9% hydrochloric acid, filtered with a vacuum filtration device, washed and filtered with deionized water, and the precipitate was dried at 80 °C for 6 hours to obtain Al-Ti3AlC2;

[0076] Al-Ti3AlC2, cadmium chloride, sodium chloride and potassium chloride were fully ground in a molar ratio of 1:6:3:3, kept reacting at 700°C for 6 hours, soaked in 10% dilute hydrochloric acid for 1 hour, and the pH of the supernatant was 6 to obtain a Ti3C2 material doped with cadmium (mass ratio was 0.6:1), the obtained Ti3C2 material was surface-modified with polyethylene glycol, and rapamycin was added (the mass ratio of rapamycin to Ti3C2 material was 0.84:1) to obtain a Ti3C2 nanomaterial loaded with rapamycin and doped with cadmium, and the molar ratio of the cadmium doped element to Ti3C2 was 0.01:1;

[0077] The obtained material is added with dodecanol, sodium hydroxide, CTAB (hexadecyltrimethylammonium bromide) and deionized water, mixed, centrifuged to remove CTAB and dodecanol, and finally the precipitate is vacuum dried to obtain light-responsive mesoporous silica.

[0078] The Ti3C2 nanomaterial loaded with rapamycin was mixed with photoresponsive mesoporous silica and added to deionized water and stirred at 2000 rpm for 24 hours. The electrostatic adsorption properties of the Ti3C2 nanomaterial and the adsorption of photoresponsive mesoporous silica were used to form a photoresponsive mesoporous silica-encapsulated Ti3C2 system loaded with rapamycin. By controlling the amount of the photoresponsive mesoporous silica-encapsulated Ti3C2 system loaded with rapamycin, artificial lenses with different concentrations of Ti3C2 (0μg / ml-500μg / ml) were obtained.

[0079] Finally, the IOL haptics were sealed with tape, the IOL was treated with O2 plasma for 5 min, immersed in Gemini surfactant for full bonding, and then the drug-loaded Ti3C2 composite material was coated on the surface of the IOL optical zone. Figure 1 The appearance of intraocular lenses loaded with different Ti3C2 concentrations and photoresponsive to rapamycin.

[0080] Effect verification test

[0081] 1. The 50 μg / ml Ti3C2 photoresponsive rapamycin intraocular lens obtained in Example 3 was exposed to 808 nm NIR (near infrared laser) at 1.0 W cm -2 Power, cumulative release curve of rapamycin after 10 minutes of irradiation. Figure 2 It can be seen that after three cycles of illumination, the cumulative release rate of rapamycin is 74.1%, while the 48-hour release of rapamycin in the artificial lens without illumination is only 19.6%. This shows that the new artificial lens obtained in Operation Example 3 can achieve light-controlled release of rapamycin.

[0082] 2. The 50 μg / ml Ti3C2 photoresponsive rapamycin intraocular lens prepared in Operation Example 3 is labeled as “element-doped Rapa@Ti3C2-IOL”.

[0083] Compared with operation example 3, no cadmium chloride is added during etching, and no cadmium element doping is formed, and "Rapa@Ti3C2-IOL" is obtained.

[0084] The artificial lens "element-doped Rapa@Ti3C2-IOL" and "Rapa@Ti3C2-IOL" were respectively exposed to 808nm NIR (near infrared laser) at 1.0Wcm -2 The power was changed and irradiated once a week for 10 min each time to obtain “element-doped Rapa@Ti3C2-IOL+Laser” and “Rapa@Ti3C2-IOL+Laser” respectively.

[0085] Commercial intraocular lenses (C-IOL), "Rapa@Ti3C2-IOL", "Rapa@Ti3C2-IOL+Laser", "element-doped Rapa@Ti3C2-IOL", and "element-doped Rapa@Ti3C2-IOL+Laser" were implanted into rabbit eyes, and the effects of inhibiting PCO were observed one month later.

[0086] IOL is artificial lens, Rapa is rapamycin, and Laser is infrared laser.

[0087] Depend on Figure 3 It can be seen that after the one-month follow-up, the cadmium-doped Ti3C2-loaded photoresponsive rapamycin artificial lens "element-doped Rapa@Ti3C2-IOL+Laser" experiment can effectively inhibit the formation of PCO in rabbit eyes through efficient photothermal effect and light-controlled release of rapamycin.

[0088] The protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.

Claims

1. Use of an artificial lens material in preparing a material for treating or preventing after-cataract, characterized in that The posterior surface of the optical zone of the intraocular lens is coated with a photoresponsive mesoporous silica-encapsulated MXene loaded with cell proliferation inhibitors, cadmium or nickel elements; Cd or Ni doped MXene is obtained by the following steps: (1) Preparation of MAX phase precursor: The metal powder represented by M in the MAX phase, the aluminum powder represented by A, and the carbide or nitride powder corresponding to M are added to a ball mill in proportion and ground, wherein an excess amount of aluminum powder is added. After sufficient grinding, the mixture is transferred to an alumina crucible, covered with graphite foil, and placed in a tube furnace for heating and reaction under an inert atmosphere to obtain Al-M n+1 AX n Sintered blocks; (2) Al-M n+1 AX n The sintered block was fully ground to obtain the precursor phase powder, which was then soaked in hydrochloric acid and washed with deionized water to remove excess metal elements. After the washing was completed, the precipitate was taken out and dried in a vacuum drying oven to obtain Al-M n+1 AX n Phase powder; (3) Molten salt etching of Al-M n+1 AX n Phase powder to obtain MXene doped with cadmium or nickel: take out the dried Al-MAX, put it into a ball mill with cadmium chloride or nickel chloride, sodium chloride and potassium chloride and grind it thoroughly, put the ground mixed powder into an alumina crucible, place it in a tube furnace, and react at high temperature under an inert atmosphere. After the reaction is completed, wash the reaction product with hydrochloric acid, filter out the solvent, take the precipitate, add deionized water and ultrasonic vibration, and then repeatedly centrifuge and wash with deionized water to obtain MXene material doped with cadmium or nickel; the molar ratio of Al-MAX, cadmium chloride or nickel chloride, NaCl and KCl is 1:1-6:3:3; the temperature of the tube furnace is 550-850°C, and the reaction time is 4-10 hours; The mass ratio of photoresponsive mesoporous silica to MXene doped with cell proliferation inhibitors, cadmium or nickel is 0.2-0.6:1; The molar ratio of doped cadmium or nickel element to MXene is 0.005-0.05:1; The preparation method of the intraocular lens material comprises the following steps: (1) MXene doped with cadmium or nickel is surface-modified with polyethylene glycol, then covalently bound with RGD peptide, and loaded with cell proliferation inhibitors to obtain MXene loaded with cell proliferation inhibitors; (2) mixing the MXene loaded with the cell proliferation inhibitor and the photoresponsive mesoporous silica, adding deionized water and stirring, to obtain the MXene loaded with the cell proliferation inhibitor encapsulated by the photoresponsive mesoporous silica; (3) MXene loaded with cell proliferation inhibitors and encapsulated in photoresponsive mesoporous silica is coated onto the posterior surface of the intraocular lens optical zone.

2. The use according to claim 1, characterized in that Cell proliferation inhibitors are nonsteroidal anti-inflammatory drugs.

3. The use according to claim 2, characterized in that The nonsteroidal anti-inflammatory drugs are COX-1 inhibitors, COX-2 inhibitors, 5-fluorouracil, methotrexate, epidermal growth factor inhibitors gefitinib or erlotinib, cyclosporine A, tacrolimus, rapamycin, paclitaxel, ROCK signaling pathway inhibitors, transforming growth factor β inhibitors and / or their siRNA or miRNA.

4. The use according to claim 1, characterized in that The mass ratio of the cell proliferation inhibitor to the MXene doped with cadmium or nickel is 0.1-1.5:1.

Citation Information

Patent Citations

  • Acidity and photothermal response type mesoporous MXene nano-sheet drug carrier and preparation method

    CN108245682A

  • Preparation method of intraocular lens material for preventing infectious intraocular inflammation

    CN114618019A